Reductive biomining of pyrite by methanogens. Issue 11 (November 2022) - Spietz, Rachel L.; Payne, Devon; Szilagyi, Robert; Boyd, Eric S.
Abstract : Pyrite (FeS2 ) is the most abundant iron sulfide mineral in Earth's crust. Until recently, FeS2 has been considered a sink for iron (Fe) and sulfur (S) at low temperature in the absence of oxygen or oxidative weathering, making these elements unavailable to biology. However, anaerobic methanogens can transfer electrons extracellularly to reduce FeS2 via direct contact with the mineral. Reduction of FeS2 occurs through a multistep process that generates aqueous sulfide (HS – ) and FeS2 -associated pyrrhotite (Fe1-x S). Subsequent dissolution of Fe1-x S provides Fe(II)(aq), but not HS –, that rapidly complexes with HS – (aq) generated from FeS2 reduction to form soluble iron sulfur clusters [ n FeS(aq) ]. Cells assimilate n FeS(aq) to meet Fe/S nutritional demands by mobilizing and hyperaccumulating Fe and S from FeS2 . As such, reductive dissolution of FeS2 by methanogens has important implications for element cycling in anoxic habitats, both today and in the geologic past. Highlights: Methanogens can reductively dissolve pyrite (FeS2 ) and mobilize iron (Fe) and sulfur (S) under anaerobic conditions. Biological reduction of FeS2 takes place via direct extracellular electron transfer (EET) that likely involves electrically conductive components of the S-layer or extracellular polymeric matrix. Fe(II) solubilized from Fe1-x S that precipitates on the surface of FeS2 during reduction combines with HS – released during FeS2 reduction to form n FeS(aq) clusters that are likely assimilated to meet Fe and S nutritional demands. Growth with FeS2 causes cells to perceive Fe limitation due to transport of n FeS(aq) rather than ionic Fe(II), thereby leading to hyperaccumulation of Fe in cells as putative thioferrate-like particles. Reduction of FeS2, assimilation of n FeS(aq), and transformation into functional biocatalysts in methanogens provides a potential path to explore the transition from abiotic, mineral-based catalysis to biocatalysis on early Earth.